DEVELOPMENT OF BENEFICIATED KAOLIN CLAY, SILVER OXIDE AND ZINC OXIDE NANOCOMPOSITE ADSORBENTS TO REMOVE CHEMICAL AND BIOCHEMICAL OXYGEN DEMANDS CONCENTRATION IN DOMESTIC WASTEWTAER - F.O, OGUNDIPE; M., SAIDU; A.S, ABDULKAREEM; A.O., BUSARI (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
This study describes the development of Beneficiated Kaolin Clay (BKC), BKC/Ag, BKC/ZnO and BKC/Ag/ZnO nanocomposite adsorbents produced by blending Silver Oxide (Ag) and Zinc Oxide (ZnO) nanoparticles with kaolin clay for removal of Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) concentration from domestic wastewater collected via sewers,High Resolution Transmission Electron Microscope (HRTEM) analysis showed that the produced adsorbents were polycrystalline in nature. The interplanar spacing and average crystalline sizes were 1.775 – 4.712 nm and 26. 834 – 40.258 nm, according to X-Ray Diffractometer (XRD) analysis. The Dispersive X – Ray Fluorescence (XRF) analysis indicated that SiO2/Al2O3 ratios for BKC/Ag, BKC/ZnO and BKC/Ag/ZnO nanocomposites adsorbents were 1.5170, 1.4818 and 1.5231 respectively. Brunauer – Emmett – Teller (BET) analysis showed that the BKC/Ag, BKC/ZnO and BKC/Ag/ZnO had a certain number of macropores (d > 50 nm) and a small amount of micropores (d < 2 nm) ascribed to mesoporous structures with hysteresis loops of type H3. The COD and BOD concentration removal efficiencies of the produced adsorbents followed this trend:BKC/Ag/ZnO > BKC/Ag > BKC/ZnO > BKC. These adsorbents were excellent in the removal of COD and BOD from domestic wastewater, and hence, recommended for large scale production.